Rebel Angels - Bray, Libba (New York : Delacorte Press, 2005)
Gemma and her friends from the Spence Academy return to the realms to defeat her foe, Circe, and to bind the magic that has been released.
Keywords: Magic -- Fiction; Supernatural -- Fiction; Private schools -- Fiction; School stories; England -- Fiction -- Social life and customs